Advancing the Quality and Status of Teaching in Australian Higher Education. - James, Richard; Baik, Chi; Millar, Victoria; Naylor, Ryan; Bexley, Emmaline; Kennedy, Gregor; Krause, Kerri-Lee; Hughes-Warrington, Marnie; Sadler, David; Booth, Sara; Booth, Carol (Office for Learning and Teaching, 2015)
The Academic Workforce 2020 project prepared a national framework and evidence-based resources to support universities in shaping a coherent agenda over the 2013-2020 period to raise the professionalism of higher education teaching. This project provided a blueprint for influencing Australian policy and practice. The project commenced with the assumption that university teaching remains only moderately professionalised. With larger and more diverse student cohorts, plus the emergence of new educational models, steps must be taken to prepare the academic workforce, itself diversifying, for a new era. Drawing on international knowledge of effective teaching, experience in the introduction of professional standards frameworks, and exemplary Australian case studies, the project consulted with the sector to propose a Framework for Academic Professionalisation that is theoretically robust and practically attainable. In articulating the core characteristics of academic professionalism, this framework will be the centrepiece for recommendations and resources to support the steps needed to advance the professionalisation of university teaching.